Dampak Rasio Keuangan Terhadap Harga Saham Perusahaan Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - Via Andani Putri; Natali Yustisia (Lisyabab : Jurnal Studi Islam dan Sosial, 2021)
This study was conducted to examine the effect of Quick Ratio, Debt to Equity Ratio, Total Asset Turnover and Return on Equity on stock prices. The population of this study are consumer goods companies listed in Indonesia Stock Exchange period 2015-2019. The sampling technique used purposive sampling and obtained a sample of 26 companies. Analytical methode used panel data regression. The result shows that Debt to Equity Ratio has a negative significant effect on stock prices while Return on Equity has a significant positive effect on stock prices. In contrast, Quick Ratio and Total Asset Turnover have no significant effect on stock prices. Meanwhile, the value of adjusted R square is 0.9619. It explains that the effect of the variables Quick Ratio, Debt to Equity Ratio, Total Asset Turnover and Return on Equity on stock prices is 96.19 percent.